RADIATION EXPOSURE IN DIFFERENT CARDIAC CATHETERIZATION PROCEDURES IN CATH LAB - Hadi, Noor -ul-; Gul, Adnan Mehmood; Ghafoor, Fazal-; Shah, Syed Tahir; Wali, Abdul; Shah, Syed Javed; Shah, Syed Sadiq; Ali, Saeed; Said, Rehman; ulla, Kashif; et al. (Journal of Ayub Medical College Abbottabad, 2013)
Background: Interventional procedures render cardiologolists and their team members to high doses of radiations. This study was conducted to assess the radiation exposure in various cardiac catheterization procedures. Methods: This descriptive cross sectional study was conducted at the catheterization laboratory of Lady Reading Hospital Peshawar from November 2008 to December 2009. Patients were categorized into four groups for procedures a. coronary angiography, b. percutaneous coronary intervention (PCI), c. permanent pacemakers (PPM) and d. percutaneous transvenous mitral commisurotomy (PTMC), two groups for operators (consultants and trainees), and three groups for various accesses (femoral, radial and sub-clavian). Results: A total of 99 patients undergoing cardiac catheterization were studied. Coronary angiography was performed in 52 (52.5%) patients, PCI in 32 (32.3%)), pacemakers in 6 (6.1%), and PTMC in 9 (9.1%) patients. Consultants did 72(72.7%) procedures and trainees did 27(27.3%) procedures. Through radial access, 22(22.2%) procedures were performed, 71(71.7%) through femoral, and 6 (6.1%) through sub-clavian. The mean radiation dose for coronary angiography was (4907.862±15231.6358 µGym2), PCI (10375.16±16083.4385 µGym2), pacemakers (1406.823±785.489 µGym2), and PTMC (1157.91±760.437 µGym2). The mean radiation dose for radial (6147.33±8480.37 µGym2), femoral (6512.58±16566.73 µGym2), and sub-clavian was (1406.82±785.48 µGym2). While for various operators consultants (7489.5±16925.55 µGym2), and trainees (2475.25±1178.86 µGym2). The mean time for radial (8.59±7.28 min), femoral (6.95±6.43 min) and sub-clavian was (8.24±4.81 min). The mean time for coronary angiography (4.56±5.32 min), PCI (11.44±6.92 min), PPM (8.24±4.81 min), and PTMC (8.28±5.01 min). Conclusions: Radiation dose varies substantially across different groups by different operators and different routes. Keywords: Radiation exposure, Radiation dose, cardiac catheterization procedures